The Effect of Internal Control System on Fraud Detection (Empirical Study at the Sumedang Regency Regional Inspectorate Office) - Cahyani, Nanda Ayu; Rahman, Erpi; Krisdina, Tiana Fenny (LPPM Universitas Sebelas April, 2025)
This study aims to identify and test the effect of the internal control system on fraud detection at the Sumedang Regency Inspectorate. This study was motivated by the problem of increasing the number of recurring findings and increasing the number of findings that have not been followed up in the last three years. The instruments used in this study were observation, interviews, and questionnaires to 22 auditors working at the Sumedang Regency Inspectorate. This study uses a quantitative method. Based on the results of the t-test, it shows that there is a significant effect of the internal control system variable on fraud detection, with the R square analysis for the internal control system partially having an effect of 87.4% on fraud detection, while the remaining 12.6% is influenced by variables not used in this study